The application of necessary but not sufficient principles to the implementation of product lifecycle management software - Van der Walt, Lizenka (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScEng (Industrial Engineering))--University of Stellenbosch, 2007.